Investigation of Biological Activity of Fucoidan and Laminarin as Bioactive Polysaccharides from Irish Brown Macroalgae - Shanmugapriya Karuppusamy; Janith Wanigasekara; Stephen Fitzpatrick; Henry Lyons; James Curtin; Gaurav Rajauria; Brijesh K. Tiwari; Colm O’Donnell (Cells)
This study aimed to investigate the biological activity of crude and purified laminarin and fucoidan samples extracted from Irish brown macroalgae species Laminaria digitata and Fucus vesiculosus. The antioxidant capacity of the samples was evaluated using the 2,2-diphenyl-1-picrylhydrazyl and ferric-reducing antioxidant power assays. The anti-inflammatory potential of the samples was analysed using the cyclooxygenases inhibition activity, and the antidiabetic activity was evaluated using a dipeptidyl peptidase-4 inhibitor screening assay. The cytotoxicity of the samples was measured using the Alamar Blue™ assay with different types of cancer cell lines. The crude laminarin and fucoidan samples exhibited higher antioxidant activity (p < 0.05) than the purified samples and commercial standards. Similarly, the crude extracts showed stronger anti-inflammatory and antidiabetic effects compared to the purified samples. Additionally, the crude laminarin and fucoidan samples showed higher cytotoxic activity. Specifically, as confirmed in the flow cytometry analysis, 3D tumour spheres using different cancer cell lines showed significantly higher resistance to bioactive compounds compared to 2D monolayer cells. The laminarin and fucoidan polysaccharide samples investigated are suitable for potential nutraceutical applications based on the biological activity values observed. Future research is necessary to purify the bioactive compounds investigated and improve their selectivity for targeted therapeutic uses in food and biomedical applications.